Women's lives in colonial Quito : gender, law, and economy in Spanish America - Gauderman, Kimberly, 1960- (University of Texas Press, 2003)
* Undermines the long-accepted patriarchal model of colonial society by uncovering the active participation of indigenous, mestiza, and Spanish women of all social classes in many aspects of civil life in seventeenth-century Quito.